Adaptive evolution of complex innovations through stepwise metabolic niche expansion - Balázs Szappanos (Nature Portfolio, 2016)
A fundamental question in evolutionary biology is how complex innovations requiring multiple genetic changes arise. Here the authors provide lines of evidence that changing environments facilitate the adaptive evolution of complex metabolic innovations via stepwise acquisition of single reactions.